Japanese Literature Students` Perspective on Weeaboo Who has an Imaginary Couple Waifu/Husbando - Hermawan, Daniel; Marciu, Rendi (Bina Nusantara University, 2024)
The phenomenon of waifu/husbando, originating from Japanese pop culture, permeated society and became a compelling subject of interest. The research delved into the perspectives of people who had a relationship with fictional characters. Data collection was done through interviews with eight students in Japanese Literature across Java Island. The research drew upon insights and data to unravel the societal perceptions surrounding waifu/husbando enthusiasts. The research applied a qualitative approach, so the analysis produced descriptive data in the form of words. The findings highlight a nuanced form of discrimination and labeling. Contrary to common assumptions, the prejudice faced by those with waifu/husbando connections is not rooted in a mere appreciation for fictional characters but extends to a broader bias against anime enthusiasts. Individuals who proudly profess their love for anime by adopting waifu/husbando are often stigmatized with the label of weeaboo, illustrating a broader societal bias against this subculture. The distinction between these two categories sheds light on the complex interplay of societal attitudes towards fantasy relationships rooted in different cultural realms. The research contributes to a deeper understanding of the intricate dynamics surrounding waifu/husbando culture and challenges prevailing stereotypes by emphasizing the role of broader societal biases against anime enthusiasts.